Cadmium removal from acqueous solution by adsorption on spent coffee grounds - Patterer, María Silvina (2017)
Cadmium is a highly toxic element and can cause serious damages to the health of human beings. It is on the seventh position on the Agency for Toxic Substances and Disease Registry (ATSDR, 2015) list for dangerous elements. The Environmental Protection Agency (EPA) and the International Agency for Research on Cancer (IARC) have also recognized cadmium as a carcinogen. For all these reasons, in the recent years stringent limits have been set for this element both in industrial and drinking water. In this paper the potential of spent coffee grounds (SCG) for the removal of cadmium from contaminated water was investigated. Batch experiments were performed at different temperatures, i.e. 10, 25 and 40°C on untreated SCG. The size range of the SCG particles studied was ≤ 500 μm. The results obtained showed that the equilibrium of cadmium on SCG was reached after 3 hours. The Langmuir isotherm provided the best correlation for the adsorption process, with a maximum adsorption capacity of 4.48 mg g-1at 10 °C. Thermodynamic analysis confirmed the exothermicity and spontaneity of the phenomenon. Kinetic studies have revealed that the cadmium adsorption onto SCG followed a pseudo-second order kinetic model and the activation energy value calculated was of 14.5 kJ mol-1, which have evidenced the physical nature of the process. Overall, this study strongly supports the use of SCG as an effective and economical adsorbent for the removal of cadmium from both industrial and drinking water.